2023
DOI: 10.3390/polym15040912
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Electrically Conductive MDF Panel—Evaluation of Carbon Content and Resin Type

Abstract: Electronics in furniture and construction materials, in particular technologies which allow for a flexible and cable-free connection of electronics in such materials, are gaining broader interest. This study shows a further development of a concept to obtain highly conductive medium-density fibreboard panels (MDF) for furniture application. MDF were produced using two mixing processes (wet and dry) for wood and carbon fibres to investigate the effects of resin type (urea formaldehyde (UF) and polymeric methyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 37 publications
(49 reference statements)
1
9
0
Order By: Relevance
“…Other studies have also reported similar behavior in the electrical properties of WBP with CF. 4,32 The CF have high electrical conductivity and can significantly increase the conductivity of the composite. 31 As the mesh area of the carbon nets decreased, the number of meshes in a certain area increased, which increased the possibilities for mutual overlapping of the carbon yarns and the formation of more conductive paths throughout the panel structure to improve the conductivity.…”
Section: Electrical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies have also reported similar behavior in the electrical properties of WBP with CF. 4,32 The CF have high electrical conductivity and can significantly increase the conductivity of the composite. 31 As the mesh area of the carbon nets decreased, the number of meshes in a certain area increased, which increased the possibilities for mutual overlapping of the carbon yarns and the formation of more conductive paths throughout the panel structure to improve the conductivity.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Other researchers have also reported an improvement in the flexural properties of wood composites with CF. 4,34,43,44 The main reason for this is that when the specimens are subjected to static loading, the top (face) of the specimens is subjected to compressive stress and the bottom of the specimens is subjected to tensile stress. Since CF have a much higher compressive and tensile strength than wood and WBP, the addition of CF leads to an improvement in the compressive and tensile strength of the reinforced composite when pressure is applied perpendicular to the surface (bending force).…”
Section: Electrical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations